P1_6 Moon Shoes on the Moon - Ramsden, Alice; Relton, Phil; Davis, Scott; Clark, Connor (Physics Special Topics, 2017)
Moon shoes are a children's toy described as 'mini trampolines for your feet'. By assuming that the rubber bands in these shoes obey Hooke's law, we have investigated how these shoes would work when used on the moon and compared this to how they work on Earth. We found that if the bands were stretched by just 0.04m, an astronaut on the moon could bounce up to 14.7m